Understanding the impacts of extreme heat on the mental well-being of older adults: a systematic review - Jifei Chen; Laurence L Delina (Environmental Research Communications)
Older adults exhibit a heightened vulnerability to the ramifications of climate change, mainly the increasing frequency and severity of extreme heat events, which can considerably impair their mental well-being. This study undertook a systematic review of scholarly databases to document older adults’ exposure to extreme heat and to evaluate the long-term outcomes on their mental health. Our analysis encompassed 22 articles, revealing several detrimental effects of extreme heat on mental well-being, including social isolation, cognitive dysfunction, affective disorders, and sleep disturbances. These adverse effects diminish the quality of life and exacerbate vulnerability to further health complications. This review underscores critical gaps in the assessment of heatwave impacts on the mental health of older individuals, especially regarding ethnicity, socioeconomic status, and cultural background. We identified significant disparities in risk levels and vulnerability experiences, which reflect entrenched societal inequalities. Future research should prioritise longitudinal studies and standardised assessment methods to enhance our understanding and resilience among older adults. Furthermore, implementing adaptive strategies—such as improved access to cooling resources, robust community support systems, and comprehensive mental health services—remains essential for assisting older adults in managing these escalating risks.